KAJIAN BAHASA RUPA PRIMADI TABRANI FOTO PORTRAIT RADEN ADIPATI SOERIA NATA NINGRAT - Hardoyo, Adityo Baskoro (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
During the colonial era of the Nusantara kingdoms, photos could be said to be a luxury item, only some people from certain groups had a photo of themselves, Raden Adipati Soeria Nata Ningrat was the one who had a portraiture photo, so it is interesting to study his photo. Studies related to portrait photos of Raden Adipati Soeria Nata Ningrat using Primadi Tabrani Bahasa Rupa have never been done before. From the portrait photo, a study can be carried out using Primadi Tabrani's Bahasa Rupa, to analyze the message to be conveyed from the photo of Raden Adipati Soeria Nata Ningrat, especially from the symbol of social status. Where the symbol of social status can be seen from the attributes of the clothes worn, such as the motifs on the clothes, the position of the keris, to the selection of batik worn in portrait photos.